A Marxian model of market for money capital: Profit rate, interest rate, and leverage ratio - Hyun Woong Park (University of Massachusetts, Department of Economics, 2020)
In this paper, I develop a Marxian model of market for money capital populated by capitalists equipped with equal money capital endowment but with heterogeneous linear production technology. Due to a maximization of return on equity, capitalists with relatively weak technology, yielding profit rate lower than interest rate, become a money capitalist (lender) and capitalists with relatively strong technology, yielding profit rate greater than interest rate, become an industrial capitalist (borrower). The equilibrium interest rate is derived by the associated demand and supply relation. In this context, Marx's notion of the role of credit system in an expanded reproduction of capital is understood in terms of an efficient reallocation of funds through credit market. From this setup of the model follow two essential relationships Marx establishes between the average profit rate and the interest rate: (i) that the profit (rate) sets a maximum limit of interest (rate), and (ii) that the two rates are correlated. Lastly, depending on the financial sector's leverage ratio, which is supported by its intermediation technology, the financial sector may be more or less profitable than the industrial sector. This result suggests that one aspect of the industrial-banking capitalists antagonism surrounding the division of profit into interest and profit of enterprise lies in the banking capitalists' strenuous efforts towards continuous innovations in financial intermediation technology.
Keywords: B51; 330; Money capital; interest-bearing capital; loanable capital; credit; interestrate